ANALISIS PENGARUH PENAMBAHAN ABU CANGKANG SAWIT TERHADAP FLEKSIBILITAS DAN DURABILITAS ASPAL MODIFIKASI PG 76 (AC-WC) - Rosyad, Farlin; Gunawan, Hizkia (Ensiklopedia of Journal, 2024)
Roads are infrastructure that plays a very important role in the progress of a region, which is a link between one region and other regions. Asphalt concrete layer (Laston) is the most frequently used road pavement in Indonesia, consisting of asphalt, aggregate and filler. In an effort to add substitutes for fine materials that can be used as ingredients in asphalt mixtures, palm shell ash, which is easily obtained, was used in research as an alternative fine material in asphalt mixtures. The asphalt used in this research is PG 76 modified asphalt originating from PT. Perdana Eternal Mighty. This research was carried out with the aim of finding out the value of a mixture of palm shell ash as a fine fraction material for AC-WC layered lastons in terms of flexibility and durability. The percentage of palm shell ash content used in this research was 0%, 4%, 6% and 8%. This research uses the Marshall test method by reviewing the effect of rice husk ash on flexibility and durability values. Based on the results of testing marshall parameters in terms of zone variations and the percentage of rice husk ash substitution content, it can be concluded that the greater the shell ash content used, the greater the flexibility and durability values, for the lowest value obtained VMA was 15.53% (residual marshall) and VIM is 4.38%. For durability, the lowest marshall quotient (MQ) value was 297 kg/mm at a palm shell ash content of 4%, while the highest marshall quotient (MQ) value was 334 kg/mm at a mixture of 8% palm shell ash content.Keywords: Rice husk ash, asphalt modified PG76, AC-WC, Flexibility, Durability